Optimizing the utilization of maize silage in forage blends-based rations to improve production performance and reduce methane emissions from fattening calves - Farooq, Khalid; Sultan, Asad; Shah, Assar Ali; Khan, Rifat Ullah; Khan, Rajwali; Yasmeen, Ghazala; Khan, Nazir Ahmad (International Journal of Agricultural and Biological Engineering, 2024)
This research investigated the effect of various mixtures of maize silage and ryegrass fodder on nutrient digestibility, production performance, and methane (CH4) emission of fattening calves. Twenty-four fattening calves ((228±10) kg body weight (BW), (280±5) d of age) were allocated to 8 diets for 84 d, according to a randomized complete block design, and the blocks were balanced for BW, age, and sex. The diets consisted of 4 levels of maize silages, i.e., 40% (MS40), 50% (MS50), 60% (MS60), and 70% (MS70) in the maize silage and ryegrass fodder mixture on a dry matter (DM) basis, and each of the mixture was supplemented with either low (LC, 1.0% BW) or high (HC, 1.5% BW) levels of fattening concentrate. The results revealed greater (p<0.05) intakes of DM (8.35 kg/d), organic matter (OM, 7.85 kg/d), and metabolizable energy (ME, 12.00 Mcal/d) in calves fed with MS70-LC diet. The highest (p<0.05) digestibility (g/100 g) of DM (65.2), OM (67.3), crude protein (69.1), and neutral detergent fibre (56.3) was recorded for MS40-HC diet. The maximum (p<0.05) average daily gain (ADG, 571 g/d) was recorded for diet MS70-LC. The lowest value (p<0.05) of CH4 emission was recorded in MS70-LC, MS70-HC, and MS60-HC as compared to other diets. Including 70% maize silage in the ryegrass-maize silage based diet improved ADG by 174 g/d with LC feeding. It is concluded that the optimum inclusion level of maize silage and ryegrass in the fattening ration can improve animal production performance and reduces CH4 production and concentrate requirements of fattening calves. Keywords: average daily gain, farm-grown forages, forage mixture, fattening calves, maize silage, ryegrass fodder DOI: 10.25165/j.ijabe.20241703.7899 Citation: Farooq K, Sultan A, Shah A A, Khan R U, Khan R, Yasmeen G, et al. Optimizing the utilization of maize silage in forage blends-based rations to improve production performance and reduce methane emissions from fattening calves. Int J Agric & Biol Eng, 2024; 17(3): 75-81.